Critical Examination of the Concept of Laḥn in Quran Recitation - Mosankore, Ali Miqdad; Shaykh Ahmad, Yahya (Al-Basirah Journal, 2024)
The recitation of the Quran forms a cardinal pillar in the daily obligatory religious duties of Muslims for spiritual upliftment. Recitation of the Quran in Prophetic manner is of great importance since emulation of the Prophet constituted an act of worship. It was however astonishing that many Muslims were unaware that it was a binding obligation to recite the Quran in accordance with the laid down rules governing it. In the contemporary society, there was wide spread cross recitation, such as mixing one version of classical recitation with another and mispronunciation of Arabic letters while reading which may alter the intended meaning. Thus, the objective of this paper was to analyze the conceptual meaning of Laḥn which was usually committed by some Quran reciters, and call the attention of the reciters to proper mastery of the science of recitation of the Quran for good recitation and understanding. Historical and phenomenological methods of research were adopted in this research. The paper revealed that the common errors in the recitation of the Quran included misapplication of the articulation of Arabic letters, and the rules guiding it among others. The paper concluded by advocating for the practical learning of application of Tajwīd, in order to avoid these common errors.